Treasure the world / Nurul Syahirah Md Yusof … [et al.] - Md Yusof, Nurul Syahirah; Abdullah, Anis Suraya; Mohd Zainy, Fatin Fasihah; Mothar, Noor Nabihah; Wan Hasan, Wan Hasmat (Division of Research and Industry Linkages, 2017)
The purpose of this product is to solve the issue of student having problem in memorizing world map and issues related. This product will be in a form of electronic interactive quiz, which the first page displays world map where users need to click the right country asked and answers the quiz given. The lecturers may use this product as teaching assistance or evaluating student’s performance regarding the knowledge involved. Student from International Business' program especially may find this quiz helpful, in a way which will provide them awareness on how their knowledge performance level about the related content. This interactive world quiz can be surely provides an assistance to users to have better understanding and excellent level of knowledge related.